Natural Killer Cells Are Characterized by the Concomitantly Increased Interferon-γ and Cytotoxicity in Acute Resolved Hepatitis B Patients - Zhao, Juanjuan; Li, Yonggang; Jin, Lei; Zhang, Shuye; Fan, Rong; Sun, Yanling; Zhou, Chunbao; Shang, Qinghua; Li, Wengang; Zhang, Zheng; Wang, Fu-Sheng (PloS one, 2012)
Natural killer (NK) cells are abundant in the liver and have been implicated in inducing hepatocellular damage in patients with chronic hepatitis B virus (HBV) infection. However, the role of NK cells in acute HBV infection remains to be elucidated. We comprehensively characterized NK cells and investigated their roles in HBV clearance and liver pathology in 19 chronic hepatitis B (CHB) patients and 21 acute hepatitis B (AHB) patients as well as 16 healthy subjects. It was found that NKp46(+) NK cells were enriched in the livers of AHB and CHB patients. We further found that peripheral NK cells from AHB patients expressed higher levels of activation receptors and lower levels of inhibitory receptors than those from CHB patients and HC subjects, thus displaying the increased cytolytic activity and interferon-γ production. NK cell activation levels were also correlated positively with serum alanine aminotransferase levels and negatively with plasma HBV DNA levels in AHB patients, which is further confirmed by the longitudinal follow-up of AHB patients. Serum pro-inflammatory cytokine and chemokine levels were also increased in AHB patients as compared with CHB and HC subjects. Thus, the concomitantly increased interferon-γ and cytotoxicity of NK cells were associated with liver injury and viral clearance in AHB patients.